MicroRNA-661 expression is upregulated in pancreatic ductal adenocarcinoma and promotes cell proliferation - Lv, Feifei (Oncol Lett, 2018)
Deregulation of microRNA (miRNA/miR) expression has been implicated in the development of pancreatic ductal adenocarcinoma (PDAC). However, the role of miR-661 in PDAC remains unknown. In the present study, it was revealed that miR-661 expression was significantly upregulated in PDAC tissues compared with that in adjacent normal tissues by using reverse transcription-quantitative polymerase chain reaction assays. Higher miR-661 expression revealed a positive association with lymph node metastasis, an advanced T stage and a poor prognosis in patients with PDAC. Furthermore, ectopic expression of miR-661 significantly promoted the cell proliferation ability in PDAC cell lines, and simultaneously promoted Wnt signaling pathway-related protein expression of β-catenin, transcription factor 4 and cyclin D1 in vitro. However, the downregulation of miR-661 revealed reverse effects. Thus, the results of the present study indicated that miR-661 may function as a prognostic marker and provide insight for pancreatic cancer treatment.